LES SOCIÉTÉS HUMAINES FACE AUX CHANGEMENTS CLIMATIQUES Volume 1 La préhistoire des origines de l'Humanité à la fin du pléistocène - Djindjian, François (2023)
The two volumes bring together the contributions of the members of the International Union of Prehistoric and Protohistoric Sciences (UISPP), to a project launched in 2017, with the support of the International Academic Union (UAI), under the title Human societies facing climate change in prehistory and protohistory: from the origins of Humanity to the beginning of historical times The first volume concerns prehistory from the earliest humans to the end of the Pleistocene, twelve thousand years ago. For three million years human societies have experienced a great alternation of glacial and interglacial periods. Which climates have been most favorable to human settlement? Which the least favorable? And did they involve the abandonment of territories, the collapse of societies and extinction of some human populations? When and in what climates did human groups colonize each of the continents of the planet? Is a period of climatic improvement with a hot and humid climate more or less favorable to the development of human societies than a period of climate depreciation? Is climate change a factor of change for human societies, forcing them to adapt and find sustainable solutions?